Main Labor Breaches of the Peruvian State in the Framework of the Free Trade Agreement with the United States - Mendoza Choque, Luis Enrique (2016)
The following article begins with the old and close relationship between labor rights and international trade, a relationship that has become more important given the creation of new instruments, mechanisms and sanctions. The labor chapter of the Peru-US Trade Promotion Agreement and its application can be analyzed from different perspectives. The following article sets its focus on three distinct facets: the principle of progressivity of social rights; the legal nature of free trade agreements; and two of the current promotional labor regimes in Peruvian legislation. The article references two complaints of non-compliance with the labor chapter presented by Peruvian unions during the period since the Free Trade Agreement entered into force. Finally, the report presents conclusions that aim to contribute to the debate on this subject.